(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2022)
Rok Vevar is a dance historian and archivist who founded the Temporary Slovene Dance Archive (TSDA) in 2011. TSDA is a platform for documenting and historicizing modern and contemporary dance in Slovenia. He first opened the archive to the public in his private apartment in Ljubljana, Slovenia, and then in March 2018, he transferred it into the premises of the Museum of Contemporary Art Metelkova in Ljubljana. The material is now more accessible to its users who are at the same time witnesses of the development of this peculiar archive. TSDA has thus become a performative, time-specific and site-specific installation presenting the archive as a structure evolving over time and without end. It seems that by entering the institutional framework as an individual, the archivist has found material support and space while retaining his relative independence. In the introduction of his article, Aldo Milohnic presents the genealogy and the structure of TSDA and then, in the main part of the article, he analyses a specific complexity of the relation artist–activist–archivist, represented by TSDA’s founder Rok Vevar.